UAV Base Station Placement Considering Type and Access Probability of Individual Nodes - Choi, Hyoungwook; Lim, Jaesung; Cheon, Hye Rm; Noh, Hongjun; Heo, Jin; Park, Hyungwon (Journal of Korean Institute of Communications and Information Sciences, 2022)
Because UAV has high mobility and quick deployment, research on UAV-BS communication and resource allocation is being actively conducted for the purpose of supporting wireless cellular networks. When each ground node has the same priority in resource allocation, a node having a high priority may not be covered. Thus, this paper proposed an UAV-BS placement algorithm that considers the type of and the channel access probability of ground node to ensure resource allocation of high priority node. UAV-BS has limited available resources by backhaul links, and ground nodes must locate within the coverage area of UAV-BS to be provided resources. In this paper, We formulate an optimization problem having a QoS requirements of backhaul links and ground nodes are considered as constraints, and object functions according to the priority of nodes and the channel access probability. We evaluated the performance through simulation and the results showed that the proposed scheme provides better coverage rate of high priority nodes and sum rate than the previously proposed algorithm based on ground node location information.
Keywords: Access probability; Base station; Optimization problem; Priority; Unmanned aerial vehicle(UAV) placement